Increased risk of open angle glaucoma in patients with moyamoya disease from a nationwide population-based cohort in Korea - Min Seok Kim; Eun Ji Lee; Si Un Lee; Tae-Woo Kim; Sang Jun Park; Se Joon Woo; Jeongwoo Lee; Seonghee Nam; Kwangsic Joo (Scientific Reports)
Abstract This nationwide population-based retrospective cohort study aims to investigate the association between Moyamoya disease (MMD) and open-angle glaucoma (OAG). In this study using the Korean National Health Insurance Service database, a total of 36,432 patients having diagnostic code with MMD between 2002 and 2022, and their age-, sex-matched non-MMD controls (n = 346,769) were included. We used a Cox proportional hazard model to determine the association between MMD and subsequent OAG after excluding cases with preexisting diagnosis of MMD for the initial 2-year. Kaplan-Meier survival analyses with log-rank test were performed to compare the incidence probability of OAG based on the MMD diagnosis. Cox regression analysis showed that the diagnosis of MMD was associated with increased risk of subsequent diagnosis of OAG (adjusted HR, 1.26; 95% CI, 1.14–1.38; P < 0.001). The cumulative incidence probability of OAG was 3.7% in MMD group and 2.9% in control group at the end of the study period, and was significantly higher among MMD patients than controls consistently during the study period (P < 0.001). In conclusion, the nationwide longitudinal data of Korean population revealed a significant association between MMD and OAG. Presence of MMD may increase the risk of developing OAG.